MAKNA KESEIMBANGAN KEHIDUPAN KERJA BAGI GENERASI MILENIAL DALAM KONTEKS BUDAYA ORGANISASI INDONESIA: KAJIAN ETNOGRAFI - Ratnawati Ratnawati; Enny Savitri; Pancagaluh Ratnasih (Jurnal Manajemen & Pendidikan [JUMANDIK], 2026)
This study examines the meaning of work-life balance for millennial employees within Indonesian organizational culture, which is deeply characterized by collectivism and hierarchical values. Although work-life balance has been extensively studied through quantitative lenses in Western contexts, understanding of how Indonesian millennials interpret, negotiate, and internalize this concept within local organizational culture frameworks remains limited. Using an ethnographic approach over eight months across three medium and large organizations in Jakarta and Surabaya, data were collected through participant observation, in-depth interviews with 24 millennial informants, and analysis of company policy documents. Findings reveal that work-life balance for Indonesian millennials is relational and contextual in nature — not merely a time-division between work and personal life, but rather a pursuit of social harmony, identity recognition, and expressive freedom within the frame of collective responsibility. This study contributes to the development of culturally sensitive work-life balance theory in non-Western contexts, while offering practical implications for human resource management in Indonesian organizations.